A rebalancing act for China and Africa : the effects of China's rebalancing on Sub-Saharan Africa's trade and growth - Chen, Wenjie; Nord, Roger; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2017)
How does China’s new growth model affect sub-Saharan Africa? To address this question, this paper first looks at the growing ties between China and Africa; attempts to estimate more precisely the impact on growth through the trade channel; and finally draws some policy implications regarding whether this means an end of the Africa Rising narrative or merely the beginning of a new chapter.​
1. Growing integration between China and Africa -- 2. A more detailed look at the trade channel -- 3. The end of Africa rising? -- Appendix -- References -- Boxes
Includes bibliographical references (pages 25-26)
Keywords: Economic development; ECONOMIC DEVELOPMENT; INTERNATIONAL ECONOMIC RELATIONS; CHINA; Africa, Sub Saharan; TRADE POLICY